Ревизия видов рода Cordylomyia (Diptera, Cecidomyiidae) фауны СССР - Мамаев, Б.М.; Рожнова, Т.А. (Вестник зоологии, 1982)
Four species of the genus Cordylomyia F e l t from the Transcarpathian area and European part of the USSR are described as new. They belong to a group characteristic by equal length of the middle antennalstem a n dbasal incrassation. C. bilobata sp. n. and C. hastagerasp. n.are similar ot C. truncata F e l t ,but the first bears a deep ventral excavation between the basal clasp segments, the second isdistinctby tegmen bearing two lanceolatelateral appendages. C .commutata sp. n. and C. obsoleta sp. n. are similarto C. rudis Winn., both having shorter antennal stems;they differ from each other by tegmen shape in the male genitalia (Figs 2, 3; 2, 4). A key to species is given.